Investigating one-handed and two-handed inter-device interaction. (October 2017) - Huang, Zheng; Limke, Jed; Kong, Jun
Abstract: Using a mobile device together with a large shared screen supports collaborative tasks and potentially prevents interference among users. In order to evaluate the usability of inter-device interaction, this paper compared two fundamental inter-device interaction styles, i.e., one-handed and two-handed interaction. The one-handed interaction style only uses one hand to select an object from a large display device while the two-handed interaction style needs the cooperation of two hands to realize a selection. A framework was developed to implement these two interaction styles. Based on the framework, a pretest-posttest, repeated-measures study was conducted to compare their differences. All participants went through eight tasks, which were differentiated by both the selection order (sequential or random order) and the density level (sparse or dense layout), using both interaction styles. During the study, both the completion time and the error rate in each task with each interaction style were recorded. In addition, the IBM Post-Study Usability Questionnaire (PSSUQ) was used to evaluate the subjective satisfaction on each interaction style. The overall PSSUQ score indicates that both interaction styles receive positive feedback with high user satisfaction. The study also revealed that the one-handed interaction took less time to complete tasks (i.e., more efficient) than the two-handed interaction, while the two-handed interaction style had a lower error rate than the one-handed interaction, and especially so in a dense layout.